2019
DOI: 10.24042/jipfalbiruni.v8i1.2536
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Newtonian Dynamics STEM-Integrated Learning Strategy to Increase Scientific Literacy of Senior High School Students

Abstract: This research aimed to examine STEM learning approach effectivity in increasing scientific literacy of senior high school students. The research involved 67Senior High School 5 students Bandar Lampung in Lampung Province, Indonesia. The research design used wasThe Non-Equivalent Control Group Pretest and Posttest Design. The experimental class used STEM Learning Approach and the control class used a scientific approach. The data was collected using pretest and posttest score of scientific literacy inventory. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…Local science can be designed into modern science, also teachers might want to engage students with positive attitude towards science. Science can be decided that process of knowledge construction and innovate their thinking to sustainability (Listiana et al, 2019;Sagala et al, 2019). Program should have more variety of activities to collaborate teachers learn how to implement STEM education into their classroom, not only focusing on knowledge or understanding how STEM education works.…”
Section: Resultsmentioning
confidence: 99%
“…Local science can be designed into modern science, also teachers might want to engage students with positive attitude towards science. Science can be decided that process of knowledge construction and innovate their thinking to sustainability (Listiana et al, 2019;Sagala et al, 2019). Program should have more variety of activities to collaborate teachers learn how to implement STEM education into their classroom, not only focusing on knowledge or understanding how STEM education works.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers can simply start with integration by analyzing students' learning behaviors, curriculum, instruction, and assessment which appropriate in different classroom. Especially, teachers have to changed mindset to classroom; learning assessment should be measured in both process and product of learning [14,18]. Teachers should allow students to have scientific knowledge and use multi-practices for making connection among necessary skills, thinking, and attributes through designed-based learning [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The concept is distributed to various kinds of school management and teachers' practice. But the result of international assessment such as TIMSS and PISA, also O-NET and other testing indicated that Thailand needs to improve students' learning quality through alternative and effective education practices [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This is certainly very much related to the expertise of teachers in developing strategies of class assessment. The goals of life skills in the 21 st -century are life and career skills, skills in technology, media, and information, as well as critical thinking skills, and innovation [26][27] [28]. Critical thinking is reflective thinking taken on the pattern of decision making about what must be agreed and must be done [29].…”
Section: Critical Thinking Skillsmentioning
confidence: 99%